2015
DOI: 10.1016/j.matdes.2015.07.121
|View full text |Cite
|
Sign up to set email alerts
|

A 3D multi-scratch test model for characterizing material removal regimes in 5083-Al alloy

Abstract: This study addresses the sensitivity of material removal regimes in 5083-Aluminum alloy to interactions mechanisms generated during Multi-Scratch Test (MST). A testing device using three conical indenters was firstly developed. Four attack angles and four normal loads ranging, respectively, in 10-60° and 10-25 N, were considered for conducting the experimental trials. The scratch velocity was kept constant to 210 mm min -1 and the maximum scratch distance to 25 mm. The model, developed upon ABAQUS/Explicit, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…It was also observed that the friction coefficient was reduced, and circumferential cracks developed around the particles. The failure modes are in accordance with simulations made by several researchers [ 14 , 15 , 16 ]. However, the models are focused on continuous and homogeneous materials free of defects, whereby the stress field in front of the tool has not been reported, nor the interaction with weaker particles, such as graphite.…”
Section: Introductionsupporting
confidence: 87%
“…It was also observed that the friction coefficient was reduced, and circumferential cracks developed around the particles. The failure modes are in accordance with simulations made by several researchers [ 14 , 15 , 16 ]. However, the models are focused on continuous and homogeneous materials free of defects, whereby the stress field in front of the tool has not been reported, nor the interaction with weaker particles, such as graphite.…”
Section: Introductionsupporting
confidence: 87%
“…The properties of Al 5083 used here were adopted from Refs. [29,30] for the dynamic response of Al 5083 and are listed in Table 1. To enhance the accuracy of the model as well as facilitate obtaining a converged plastic strain distribution, a finer mesh was used in and around the pulse area where elements of 0.05 mm × 0.05 mm × 0.03 mm were chosen (Figure 1).…”
Section: D Simulation Of the Laser Peening Processmentioning
confidence: 99%
“…Traditionally, mesh-based finite element methods (FEM) have been preferred to model single asperity sliding in scratch tests. In modelling a highly dynamic and large scale deformation problem such as scratching, the selected explicit FE packages have used adaptive remeshing, element deletion and differential meshing to deal with problems of element distortion and high computational cost [10][11][12][13]. Ploughing models in the commercial FE packages have mostly used time-independent bilinear elastic-linearly hardening and Johnson-Cook material models and Columbic frictional contact at the interface [14,15].…”
Section: Introductionmentioning
confidence: 99%